Riches of the forest: fruits, remedies and handicrafts in Latin America - López, C.; Shanley, P.; Fantini, A.C. (Center for International Forestry Research, 2004)
This book compiles traditional and specialized knowledge about 26 plants used by rural and urban people in Latin America. The pages tell real-life stories about a wide range of forest products and the people who use and manage them. The book describes what we can learn from the people who carve out a living harvesting these forest products? The individual chapters illustrate how different forest foods, fibres and medicines are grown, harvested, processed and traded. Through these stories we learn about the history of such products - some of which have been used and traded for centuries, while others are relatively new. It also shows the various opportunities and problems that collectors and traders face, and the way they respond to change. In each case, the book describes the main characteristics of the forest product, its historical usage, harvesting and management, and how it is processed and traded. In closing, each author comments briefly on trends and current issues regarding the resource. The final chapter reviews common themes and lessons that can be drawn from these cases.